Analisis kesulitan siswa dalam pembelajaran matematika menggunakan model pembelajaran inkuiri - Intan Khadijah Simatupang; Suci Dahlya Narpila (Mahesa Research Center, 2023)
One of the learning models that can be applied in the 2013 curriculum is the inquiry learning model. By using the inquiry learning model which can build student activity in participating in mathematics learning, it is very necessary in inquiry learning so that mathematics can become a fun lesson. The same thing is also based on observations at the Mawaridussalam Islamic boarding school Batang Kuis showing that educators have carried out for one semester using the Inquiry Based Learning model. However, students experience difficulties in learning Mathematics. This is caused by differences in student learning outcomes with students' understanding abilities. The method used in this research is qualitative method. In this study, the subjects were all VII-C class students at the Mawaridussalam Islamic Boarding School for the 2022/2023 academic year with a total of 25 students. This research uses a descriptive method by describing students' difficulties in learning mathematics using the Inquiry Based Learning model in class VII-C of the Mawaridussalam Islamic Boarding School in the 2022/2023 academic year. The results of the study indicate that there are several difficulties faced by students in learning mathematics in using the inquiry learning model at the Mawaridussalam Islamic boarding school, namely: (1) technical difficulties, including the learning process which is carried out in a long way (2) students' adaptation difficulties, including feeling bored, embarrassed to ask friends, and difficult to understand learning (3) difficulties in the condition of the teacher, including the lack of preparation in lesson planning.